Clock recovery and demultiplexing of high-speed OTDM signal through combined use of bismuth oxide nonlinear fiber and erbium-doped bismuth oxide fiber - Lee, JH; Ohara, S; Nagashima, T; Hasegawa, T; Sugimoto, N; Igarashi, K; Katoh, K; Kikuchi, K (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2005)
We explore the ultimate potential offered by state-of-the-art Bismuth oxide-based optical fiber technology in a high-speed optical phase-locked loop-based clock recovery subsystem for an optical time-division multiplexed (OTDM) signal, in which the use of optical fiber-based devices has been considered to be inappropriate due to its tight requirement of short optical loop length. Here, we experimentally demonstrate the implementation of a compact all-fiber-based OTDM receiver incorporating both clock recovery and demultiplexing functions by use of short lengths of Bismuth oxide-based nonlinear fiber and erbium-doped Bismuth oxide fiber. Successful clock recovery and subsequent error-free demultiplexing are readily achieved at a data rate of 80 Gb/s. The clock recovery subsystem is also shown to be operable at 160 Gb/s.